The Importance of Employing Critical Thinking in the Development of Speaking Abilities - Halima Muhammadiyeva Saidahmadovna (Scientific Trends, 2024)
Critical thinking is one of the major and rapidly growing concepts in education. Today, its role in second and foreign language learning and teaching is of great importance. Critical thinking skills and the mastery of the English language are expected to become essential outcomes of university education. To become fluent in a language and must be able to think critically and express thoughts, students need practice speaking activities using critical thinking skills. In this article, we define the concept “critical thinking” and discuss the role of critical thinking in the development of speaking skills through some practical activities that can be used in the classroom for students to practice critical thinking skills.
Keywords: Critical thinking (CT), speaking skills, ability, discussion, EFL teacher, Ted Talks.